Model-Driven Engineering Support For Product Line Engineering - Elsner, Christoph; Groher, Iris; Fiege, Ludger; Völter, Markus (Aspect-Oriented, Model-Driven Software Product Lines - The AMPLE Way, 2011)
This chapter describes our approach for mapping the requirements processed by AMPLE techniques and tools, such as ArborCraft (Chapter 3), VML4RE (Chapter 5) and HAM (Chapter 5), to a product line architecture. In contrast to the implementation-related Chapter 6, which focuses on CaesarJ for implementing configurable software components, this chapter concentrates on a model-driven approach based on variability modelling, domain-specific languages (DSLs), architecture blueprints and templates, and libraries of artefacts (arbitrary software components, configuration and deployment data, etc.).Model-driven engineering (MDE) is an approach that captures the key features of the system used in models, and develops and refines these models during development until code is finally generated. Models are defined at different conceptual levels, and are combined and transformed from a higher level of abstraction to a more concrete one. By integrating MDE into software product line engineering (SPLE), solution space artefacts can be systematically derived from problem space concepts, leading to a higher automation in application engineering saving cost and time. Models abstract the problem and facilitate rigorous descriptions using terms and concepts that are familiar to people who work in the domain of the problem, rather than in terms only familiar to IT experts. In particular, essential improvements can be achieved by using DSLs to represent the system design with terminology and abstractions of the problem domain, which is easier to understand for problem domain experts.
UnivIS-Import:2015-04-20:Pub.2011.tech.IMMD.IMMD4.modeld